2011
DOI: 10.1002/cncr.25837
|View full text |Cite
|
Sign up to set email alerts
|

A clustered ground‐glass hepatocyte pattern represents a new prognostic marker for the recurrence of hepatocellular carcinoma after surgery

Abstract: BACKGROUND:The recurrence of hepatocellular carcinoma (HCC) after hepatectomy is a serious event. It has been demonstrated that different ground-glass hepatocyte (GGH) patterns harbor specific hepatitis B virus (HBV) pre-S deletion mutants and represent preneoplastic lesions in chronic HBV infection. In the current study, the authors investigated whether a specific GGH pattern in nontumorous liver tissues was associated with the recurrence of HBVrelated HCC after surgery. METHODS: Clinicopathologic data from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 90 publications
4
73
0
Order By: Relevance
“…Almost all the untreated CHB patients harbored HBsAg-negative hepatocytes in their livers, and the distribution of HBsAg-positive cells was scattered or clustered (Fig. 6A), which was consistent with previous reports121314. The frequency of HBsAg-positive hepatocytes was positively correlated with serum HBV DNA and HBsAg levels in treatment-naïve CHB patients (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Almost all the untreated CHB patients harbored HBsAg-negative hepatocytes in their livers, and the distribution of HBsAg-positive cells was scattered or clustered (Fig. 6A), which was consistent with previous reports121314. The frequency of HBsAg-positive hepatocytes was positively correlated with serum HBV DNA and HBsAg levels in treatment-naïve CHB patients (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The anti‐HBS antibody (clone T9; Thermo Fisher Scientific), which recognized the major HBS region, and the in‐house developed anti‐LHBS antibody, which recognized the pre‐S 1 region, were used as the primary antibodies. The protocol of the IHC staining analysis followed that described . Briefly, the procedures were done with the Benchmark XT autostainer (Ventana Medical Systems Inc.).…”
Section: Methodssupporting
confidence: 88%
“…Type II GGH has therefore been hypothesized as a preneoplastic change in chronic carriers and in the peritumorous regions of HCC . We also recently reported that clustered type II GGHs in HCC are correlated with higher tumor recurrence rates in patients who underwent a hepatic resection, which indicates that the pre‐S 2 mutant LHBS is important for HCC progression . Other studies have also reported that HBV carriers who presented with pre‐S 2 mutant LHBS in serum were predisposed to advanced liver diseases, including liver cirrhosis and HCC.…”
mentioning
confidence: 99%
“…All these changes eventually result in hepatocarcinogenesis. In peritumoral tissues, a preS deletion at nt.107-141 and preS2 mutations are independently associated with poor DFS and OS after surgery (23, 30). A1762T/G1764A in liver tissue can independently predict postoperative survival (15).…”
Section: Evidence Acquisitionmentioning
confidence: 99%